1982
DOI: 10.1002/jcp.1041120105
|View full text |Cite
|
Sign up to set email alerts
|

The relation between protein accumulation and cell cycle traverse of human NHIK 3025 cells in unbalanced growth

Abstract: Human NHIK 3025 cells, synchronized by mitotic selection, were given 2 mM thymidine, which inhibited DNA synthesis without reducing the rate of protein accumulation. After removal of the thymidine the cells proceeded towards mitosis and cell division, with an S duration 2 hours shorter than, but a G2 and M duration nearly identical to that of the control cells. If cycloheximide (1.25 muM) was present together with thymidine, no net protein accumulation took place during the treatment, and the subsequent durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…30 The value of t B can be estimated as follows: at maximum growth rate, practically all cells are cycling. Therefore, the noncycling fraction,fo, can be neglected.…”
Section: Calculation Of Trrmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The value of t B can be estimated as follows: at maximum growth rate, practically all cells are cycling. Therefore, the noncycling fraction,fo, can be neglected.…”
Section: Calculation Of Trrmentioning
confidence: 99%
“…The constant duration of phase B, tB, is approximately equal to the minimum time required for a cell to traverse the entire cycle. 30 The value of t B can be estimated as follows: at maximum growth rate, practically all cells are cycling. Therefore, the noncycling fraction,fo, can be neglected.…”
Section: Calculation Of Trrmentioning
confidence: 99%
“…The existence of an irreducible length of G1 period in CHO (Stancel et al, 1981), HeLa, and AKR-MCA cells (present study) after hydroxyurea treatment suggests that certain events during G1 period have to be completed in order for a cell to initiate DNA synthesis. Ronning and Seglen (1982), who studied the effects of synchronization of human NHIK 3025 cells by excess thymidine treatment on the duration of GI phase in the subsequent cycle, came to a similar conclusion.…”
Section: Discussionmentioning
confidence: 70%
“…Smith and Martin model considered here has sound experimental confirmation (Robinson et al, 1976;Shields, 1978;Shields et al, 1978;Ronning and Seglen, 1982;Rabinovich, 1983) and served as a basis for theoretical models describing the curves of labeled mitoses (Cain and Chau, 1997). We have demonstrated that the model of Smith and Martin is less accurate in describing our experimental data than is our model ascribing the major role in the heterogeneity of proliferation rates to the dispersion of the rates of cell-cycle progression in a deterministic phase.…”
Section: Discussionmentioning
confidence: 79%